RECIDIVITY IN CRIMINAL LAW: EXPERIENCE OF UZBEKISTAN AND FOREIGN COUNTRIES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article provides a comparative analysis of the concept of recidivism, an important institution of criminal law, its types, legal consequences and its place in national legislation using the example of Uzbekistan and foreign countries. The author reveals the theoretical foundations of recidivism, its importance in determining punishment, as well as existing problems and shortcomings in this area. In particular, the legislation of the CIS countries such as Uzbekistan, Russia, Kazakhstan, Belarus, as well as Japan, China, the USA and European countries is compared. As a result of the study, effective mechanisms for combating recidivism are proposed.